Preparation and in vivo evaluation of glyco-gold nanoparticles carrying synthetic mycobacterial hexaarabinofuranoside - Burygin, Gennady L.; Abronina, Polina I.; Podvalnyy, Nikita M.; Staroverov, Sergey A.; Kononov, Leonid O.; Dykman, Lev A. (Beilstein Journal of Nanotechnology, 2020)
A number of bacterial glycans are specific markers for the detection and the serological identification of microorganisms and are also widely used as antigenic components of vaccines. The use of gold nanoparticles as carriers for glyco-epitopes is becoming an important alternative to the traditional conjugation with proteins and synthetic polymers. In this study, we aimed to prepare and evaluate in vivo glyco-gold nanoparticles (glyco-GNPs) bearing the terminal-branched hexaarabinofuranoside fragment (Ara6) of arabinan domains of lipoarabinomannan and arabinogalactan, which are principal polysaccharides of the cell wall of Mycobacterium tuberculosis, the causative agent of tuberculosis. In particular, we were interested whether the antibodies generated against Ara6-GNPs would recognize the natural saccharides on the cell surface of different mycobacterial strains. Two synthetic Ara6 glycosides with amino-functionalized spacer aglycons differing in length and hydrophilicity were directly conjugated with spherical gold nanoparticles (d = 15 nm) to give two sets of glyco-GNPs, which were used for the immunization of rabbits. Dot assays revealed cross-reactions between the two obtained antisera with the hexaarabinofuranoside and the 2-aminoethyl aglycon used for the preparation of glyco-GNPs. Both antisera contained high titers of antibodies specific for Mycobacteria as shown by enzyme-linked immunosorbent assay using M. bovis and M. smegmatis cells as antigens while there was only a weak response to M. phlei cells and no interaction with E. coli cells. The results obtained suggest that glyco-GNPs are promising agents for the generation of anti-mycobacterial antibodies.
Keywords: conjugation of glycosides; gold nanoparticles; lipoarabinomannan; Mycobacterium; spacer aglycon

Bacterial lipopolysaccharides: structure, chemical synthesis, biogenesis and interaction with host cells - Knirel, Y. A.; Valvano, M. A. (Springer Vienna, 2011)

Essentials of glycobiology - Varki, A.; Cummings, R. D.; Esko, J. D.; Stanley, P.; Hart, G. W.; Aebi, M.; Darvill, A. G.; Kinoshita, T.; Packer, N. H.; Prestegard, J. H.; Schnaar, R. L.; Seeberger, P. H. (Cold Spring Harbor Laboratory Press, 2017)
Available from: https://www.ncbi.nlm.nih.gov/books/NBK310274 (accessed Dec 8, 2019).

(untitled) - Schloter, M.; Aßmus, B.; Hartmann, A. (Biotechnol. Adv., 1995)

(untitled) - Chen, M.; Shpirt, A. M.; Guo, X.; Shashkov, A. S.; Zhuang, Y.; Wang, L.; Knirel, Y. A.; Liu, B. (Microbiology (London, U. K.), 2015)

(untitled) - Mistou, M.-Y.; Sutcliffe, I. C.; van Sorge, N. M. (FEMS Microbiol. Rev., 2016)

Carbohydrate-Based Vaccines - Roy, R. (American Chemical Society, 2008)

Carbohydrate-Based Vaccines - Kim, H.-S.; Ng, E. S. M.; Zheng, R. B.; Whittal, R. M.; Schriemer, D. C.; Lowary, T. L. (Studies toward the development of anti-tuberculosis vaccines based on mycobacterial lipoarabinomannan, 2008)

(untitled) - Buskas, T.; Thompson, P.; Boons, G.-J. (Chem. Commun., 2009)

(untitled) - Guo, Z.; Wang, Q. (Curr. Opin. Chem. Biol., 2009)

Carbohydrate Chemistry - Tam, P.-H.; Lowary, T. L. (Mycobacterial lipoarabinomannan fragments as haptens for potential anti-tuberculosis vaccines, 2010)

Comprehensive Natural Products II - Wang, Q.; Guo, Z. (Carbohydrate Vaccines, 2010)

(untitled) - Wang, Q.; Guo, Z. (ACS Med. Chem. Lett., 2011)

(untitled) - Yu, S.; Wang, Q.; Zhang, J.; Wu, Q.; Guo, Z. (Med. Chem. Commun., 2011)

(untitled) - Wang, Q.; Zhou, Z.; Tang, S.; Guo, Z. (ACS Chem. Biol., 2012)

(untitled) - Peri, F. (Chem. Soc. Rev., 2013)

Carbohydrate Chemistry - Valdés Balbin, Y.; Rodríguez, M. C.; Verez Bencomo, V. (Chapter 26. Antibacterial and antifungal vaccines based on synthetic oligosaccharides, 2014)

(untitled) - Bhatia, S.; Dimde, M.; Haag, R. (Med. Chem. Commun., 2014)

(untitled) - Zhou, Z.; Mondal, M.; Liao, G.; Guo, Z. (Org. Biomol. Chem., 2014)

(untitled) - Wang, L.; Feng, S.; An, L.; Gu, G.; Guo, Z. (J. Org. Chem., 2015)

(untitled) - Zhou, Z.; Liao, G.; Mandal, S. S.; Suryawanshi, S.; Guo, Z. (Chem. Sci., 2015)

(untitled) - Liao, G.; Zhou, Z.; Suryawanshi, S.; Mondal, M. A.; Guo, Z. (ACS Cent. Sci., 2016)

(untitled) - Zhou, Z.; Mandal, S. S.; Liao, G.; Guo, J.; Guo, Z. (Sci. Rep., 2017)

(untitled) - Wang, L.; Feng, S.; Wang, S.; Li, H.; Guo, Z.; Gu, G. (J. Org. Chem., 2017)

(untitled) - Daniel, M.-C.; Astruc, D. (Chem. Rev., 2004)

(untitled) - Dykman, L.; Khlebtsov, N. (Chem. Soc. Rev., 2012)

(untitled) - Sapsford, K. E.; Algar, W. R.; Berti, L.; Gemmill, K. B.; Casey, B. J.; Oh, E.; Stewart, M. H.; Medintz, I. L. (Chem. Rev., 2013)

(untitled) - Barrientos, Á. G.; de la Fuente, J. M.; Rojas, T. C.; Fernandez, A.; Penades, S. (Chem. – Eur. J., 2003)

(untitled) - Rojo, J.; Díaz, V.; de la Fuente, J. M.; Segura, I.; Barrientos, A. G.; Riese, H. H.; Bernad, A.; Penadés, S. (ChemBioChem, 2004)

(untitled) - de la Fuente, J. M.; Penadés, S. (Biochim. Biophys. Acta, Gen. Subj., 2006)

(untitled) - Ojeda, R.; de Paz, J. L.; Barrientos, A. G.; Martín-Lomas, M.; Penadés, S. (Carbohydr. Res., 2007)

(untitled) - García, I.; Marradi, M.; Penadés, S. (Nanomedicine (London, U. K.), 2010)

Advances in Carbohydrate Chemistry and Biochemistry - Marradi, M.; Martin-Lomas, M.; Penades, S. (Glyconanoparticles: polyvalent tools to study carbohydrate-based interactions, 2010)

(untitled) - Safari, D.; Marradi, M.; Chiodo, F.; Dekker, H. A. T.; Shan, Y.; Adamo, R.; Oscarson, S.; Rijkers, G. T.; Lahmann, M.; Kamerling, J. P.; Penadés, S.; Snippe, H. (Nanomedicine (London, U. K.), 2012)

(untitled) - Safari, D.; Marradi, M.; Chiodo, F.; Dekker, H. A. T.; Shan, Y.; Adamo, R.; Oscarson, S.; Rijkers, G. T.; Lahmann, M.; Kamerling, J. P.; Penadés, S.; Snippe, H. (Nanomedicine (London, U. K.), 2012)

(untitled) - Brinãs, R. P.; Sundgren, A.; Sahoo, P.; Morey, S.; Rittenhouse-Olson, K.; Wilding, G. E.; Deng, W.; Barchi, J. J., Jr (Bioconjugate Chem., 2012)

(untitled) - Reichardt, N. C.; Martín-Lomas, M.; Penadés, S. (Chem. Soc. Rev., 2013)

(untitled) - Parry, A. L.; Clemson, N. A.; Ellis, J.; Bernhard, S. S. R.; Davis, B. G.; Cameron, N. R. (J. Am. Chem. Soc., 2013)

(untitled) - Bernardi, A.; Jiménez-Barbero, J.; Casnati, A.; De Castro, C.; Darbre, T.; Fieschi, F.; Finne, J.; Funken, H.; Jaeger, K.-E.; Lahmann, M.; Lindhorst, T. K.; Marradi, M.; et al. (Chem. Soc. Rev., 2013)

(untitled) - Marradi, M.; Chiodo, F.; García, I.; Penadés, S. (Chem. Soc. Rev., 2013)

(untitled) - Reynolds, M.; Marradi, M.; Imberty, A.; Penadés, S.; Pérez, S. (Glycoconjugate J., 2013)

(untitled) - Adak, A. K.; Li, B.-Y.; Lin, C.-C. (Carbohydr. Res., 2015)

(untitled) - Gregory, A. E.; Judy, B. M.; Qazi, O.; Blumentritt, C. A.; Brown, K. A.; Shaw, A. M.; Torres, A. G.; Titball, R. W. (Nanomedicine (N. Y., NY, U. S.), 2015)

(untitled) - Poonthiyil, V.; Golovko, V. B.; Fairbanks, A. J. (Org. Biomol. Chem., 2015)

(untitled) - Poonthiyil, V.; Nagesh, P. T.; Husain, M.; Golovko, V. B.; Fairbanks, A. J. (ChemistryOpen, 2015)

(untitled) - Reichardt, N.-C.; Martín-Lomas, M.; Penadés, S. (Chem. Commun., 2016)

(untitled) - Compostella, F.; Pitirollo, O.; Silvestri, A.; Polito, L. (Beilstein J. Org. Chem., 2017)

(untitled) - Vetro, M.; Safari, D.; Fallarini, S.; Salsabila, K.; Lahmann, M.; Penadés, S.; Lay, L.; Marradi, M.; Compostella, F. (Nanomedicine (London, U. K.), 2017)

(untitled) - Poonthiyil, V.; Lindhorst, T. K.; Golovko, V. B.; Fairbanks, A. J. (Beilstein J. Org. Chem., 2018)

Neoglycoconjugates: preparation and application - Magnusson, G.; Chernyak, A. Y.; Kihlberg, J.; Kononov, L. O. (Synthesis of neoglycoconjugates, 1994)

Glycoproteins II - Lee, R. T.; Lee, Y. C. (Neoglycoproteins, 1997)

Carbohydrate chemistry - Roy, R. (The chemistry of neoglycoconjugates, 1998)

(untitled) - Bovin, N. V. (Glycoconjugate J., 1998)

Advances in Carbohydrate Chemistry and Biochemistry - Chabre, Y. M.; Roy, R. (Design and creativity in synthesis of multivalent neoglycoconjugatesa, 2010)

(untitled) - Miura, Y. (Polym. J., 2012)

(untitled) - Solís, D.; Bovin, N. V.; Davis, A. P.; Jiménez-Barbero, J.; Romero, A.; Roy, R.; Smetana, K., Jr; Gabius, H.-J. (Biochim. Biophys. Acta, Gen. Subj., 2015)

(untitled) - Dykman, L. A.; Khlebtsov, N. G. (Chem. Sci., 2017)

Gold nanoparticles in biomedical applications - Dykman, L.; Khlebtsov, N. (CRC Press, 2018)

(untitled) - Salazar-González, J. A.; González-Ortega, O.; Rosales-Mendoza, S. (Expert Rev. Vaccines, 2015)

Tuberculosis (TB) - World Health Organization

Tuberculosis Fact Sheet No. 104 - World Health Organization

(untitled) - Coker, R. J. (Trop. Med. Int. Health, 2004)

(untitled) - Paolo, W. F., Jr; Nosanchuk, J. D. (Lancet Infect. Dis., 2004)

(untitled) - Davies, P. D. O. (Ann. Med. (Abingdon, U. K.), 2003)

(untitled) - Brennan, P. J.; Brosch, R.; Birren, B.; Sobral, B. (Tuberculosis, 2013)

(untitled) - Murase, T.; Zheng, R. B.; Joe, M.; Bai, Y.; Marcus, S. L.; Lowary, T. L.; Ng, K. K. (J. Mol. Biol., 2009)

(untitled) - Lowary, T. L. (Acc. Chem. Res., 2016)

(untitled) - Frens, G. (Nature (London), Phys. Sci., 1973)

(untitled) - Leff, D. V.; Brandt, L.; Heath, J. R. (Langmuir, 1996)

(untitled) - de la Llave, E.; Clarenc, R.; Schiffrin, D. J.; Williams, F. J. (J. Phys. Chem. C, 2014)

(untitled) - Cai, H.; Yao, P. (Colloids Surf., B, 2014)

(untitled) - Kulandaisamy, A. J.; Rayappan, J. B. B. (J. Nanosci. Nanotechnol., 2018)

(untitled) - Selvakannan, P. R.; Mandal, S.; Phadtare, S.; Pasricha, R.; Sastry, M. (Langmuir, 2003)

(untitled) - Zhong, Z.; Patskovskyy, S.; Bouvrette, P.; Luong, J. H. T.; Gedanken, A. (J. Phys. Chem. B, 2004)

(untitled) - Porta, F.; Krpetić, Z.; Prati, L.; Gaiassi, A.; Scarì, G. (Langmuir, 2008)

(untitled) - Aghdam, A. G.; Vossoughi, M.; Almzadeh, I.; Zeinali, M. (J. Dispersion Sci. Technol., 2008)

(untitled) - Hamaguchi, K.; Kawasaki, H.; Arakawa, R. (Colloids Surf., A, 2010)

(untitled) - Dykman, L. A.; Staroverov, S. A.; Mezhenny, P. V.; Fomin, A. S.; Kozlov, S. V.; Volkov, A. A.; Laskavy, V. N.; Shchyogolev, S. Y. (Gold Bull., 2015)

(untitled) - Titanova, E. O.; Burygin, G. L. (Proc. SPIE, 2015)

(untitled) - Morrow, B. J.; Matijević, E.; Goia, D. V. (J. Colloid Interface Sci., 2009)

(untitled) - Simeonova, S.; Georgiev, P.; Exner, K. S.; Mihaylov, L.; Nihtianova, D.; Koynov, K.; Balashev, K. (Colloids Surf., A, 2018)

(untitled) - Chen, F.; Li, X.; Hihath, J.; Huang, Z.; Tao, N. (J. Am. Chem. Soc., 2006)

(untitled) - Yochelis, S.; Katzir, E.; Kalcheim, Y.; Gutkin, V.; Millo, O.; Paltiel, Y. (J. Nanotechnol., 2012)

(untitled) - Lee, S. H.; Bae, K. H.; Kim, S. H.; Lee, K. R.; Park, T. G. (Int. J. Pharm., 2008)

(untitled) - Cecioni, S.; Praly, J.-P.; Matthews, S. E.; Wimmerová, M.; Imberty, A.; Vidal, S. (Chem. – Eur. J., 2012)

(untitled) - Cecioni, S.; Imberty, A.; Vidal, S. (Chem. Rev., 2015)

(untitled) - Ligeour, C.; Dupin, L.; Angeli, A.; Vergoten, G.; Vidal, S.; Meyer, A.; Souteyrand, E.; Vasseur, J.-J.; Chevolot, Y.; Morvan, F. (Org. Biomol. Chem., 2015)

(untitled) - Wang, S.; Dupin, L.; Noël, M.; Carroux, C. J.; Renaud, L.; Géhin, T.; Meyer, A.; Souteyrand, E.; Vasseur, J.-J.; Vergoten, G.; Chevolot, Y.; Morvan, F.; et al. (Chem. – Eur. J., 2016)

(untitled) - Angeli, A.; Li, M.; Dupin, L.; Vergoten, G.; Noël, M.; Madaoui, M.; Wang, S.; Meyer, A.; Géhin, T.; Vidal, S.; Vasseur, J.-J.; Chevolot, Y.; et al. (ChemBioChem, 2017)

(untitled) - Angeli, A.; Dupin, L.; Madaoui, M.; Li, M.; Vergoten, G.; Wang, S.; Meyer, A.; Géhin, T.; Vidal, S.; Vasseur, J.-J.; Chevolot, Y.; Morvan, F. (ChemistrySelect, 2017)

(untitled) - Bagul, R. S.; Hosseini, M.; Shiao, T. C.; Saadeh, N. K.; Roy, R. (Polym. Chem., 2017)

(untitled) - Svedhem, S.; Öhberg, L.; Borrelli, S.; Valiokas, R.; Andersson, M.; Oscarson, S.; Svensson, S. C. T.; Liedberg, B.; Konradsson, P. (Langmuir, 2002)

(untitled) - Abronina, P. I.; Podvalnyy, N. M.; Mel’nikova, T. M.; Zinin, A. I.; Fedina, K. G.; Kachala, V. V.; Torgov, V. I.; Kononov, L. O.; Panfertsev, E. A.; Baranova, E. V.; Mochalov, V. V.; Dyatlova, V. I.; et al. (Russ. Chem. Bull., 2010)

(untitled) - Podvalnyy, N. M.; Abronina, P. I.; Fedina, K. G.; Kondakov, N. N.; Zinin, A. I.; Chizhov, A. O.; Torgov, V. I.; Kachala, V. V.; Kononov, L. O. (Russ. Chem. Bull., 2015)

Advanced Techniques in Biological Electron Microscopy III - De Mey, J.; Moeremans, M. (The preparation of colloidal gold probes and their use as marker in electron microscopy, 1986)

(untitled) - Staroverov, S. A.; Dykman, L. A. (Nanotechnol. Russ., 2013)

(untitled) - Dykman, L. A.; Staroverov, S. A.; Fomin, A. S.; Khanadeev, V. A.; Khlebtsov, B. N.; Bogatyrev, V. A. (Int. Immunopharmacol., 2018)

(untitled) - Thiele, H.; Hoppe, K.; Moll, G. (Kolloid Z. Z. Polym., 1962)

(untitled) - Chow, M. K.; Zukoski, C. F. (J. Colloid Interface Sci., 1994)

(untitled) - Konnova, O. N.; Boiko, A. S.; Burygin, G. L.; Fedonenko, Y. P.; Matora, L. Y.; Konnova, S. A.; Ignatov, V. V. (Microbiology (London, U. K.), 2008)

(untitled) - Bolarinwa, I. F. (J. Food Prot., 2015)

(untitled) - Chen, Y.-S.; Hung, Y.-C.; Lin, W.-H.; Huang, G. S. (Nanotechnology, 2010)

(untitled) - Shiosaka, S.; Kiyama, H.; Wanaka, A.; Masaya, T. (Brain Res., 1986)

(untitled) - Kim, B.-J.; Lee, S.-H.; Lyu, M.-A.; Kim, S.-J.; Bai, G.-H.; Kim, S.-J.; Chae, G.-T.; Kim, E.-C.; Cha, C.-Y.; Kook, Y.-H. (J. Clin. Microbiol., 1999)

(untitled) - Kononov, L. O. (RSC Adv., 2015)

(untitled) - Kononov, L. O.; Malysheva, N. N.; Orlova, A. V.; Zinin, A. I.; Laptinskaya, T. V.; Kononova, E. G.; Kolotyrkina, N. G. (Eur. J. Org. Chem., 2012)

Advances in Chemistry Research - Kononov, L. O. (Modulation of Stereoselectivity of Glycosylation: A Supramer Approach, 2013)

(untitled) - Abronina, P. I.; Zinin, A. I.; Romashin, D. A.; Tereshina, V. V.; Chizhov, A. O.; Kononov, L. O. (Carbohydr. Res., 2018)

(untitled) - Podvalnyy, N. M.; Malysheva, N. N.; Panova, M. V.; Zinin, A. I.; Chizhov, A. O.; Orlova, A. V.; Kononov, L. O. (Carbohydr. Res., 2017)

(untitled) - Orlova, A. V.; Laptinskaya, T. V.; Bovin, N. V.; Kononov, L. O. (Russ. Chem. Bull., 2017)

(untitled) - Nagornaya, M. O.; Orlova, A. V.; Stepanova, E. V.; Zinin, A. I.; Laptinskaya, T. V.; Kononov, L. O. (Carbohydr. Res., 2018)

(untitled) - Orlova, A. V.; Andrade, R. R.; da Silva, C. O.; Zinin, A. I.; Kononov, L. O. (ChemPhysChem, 2014)

(untitled) - Orlova, A. V.; Tsvetkov, D. E.; Kononov, L. O. (Russ. Chem. Bull., 2017)

(untitled) - Fallarini, S.; Paoletti, T.; Battaglini, C. O.; Ronchi, P.; Lay, L.; Bonomi, R.; Jha, S.; Mancin, F.; Scrimin, P.; Lombardi, G. (Nanoscale, 2013)

(untitled) - Abronina, P. I.; Zinin, A. I.; Orlova, A. V.; Sedinkin, S. L.; Kononov, L. O. (Tetrahedron Lett., 2013)

(untitled) - Kunishima, M.; Kawachi, C.; Hioki, K.; Terao, K.; Tani, S. (Tetrahedron, 2001)

(untitled) - Kunishima, M.; Hioki, K.; Wada, A.; Kobayashi, H.; Tani, S. (Tetrahedron Lett., 2002)

(untitled) - DuBois, M.; Gilles, K. A.; Hamilton, J. K.; Rebers, P. A.; Smith, F. (Anal. Chem. (Washington, DC, U. S.), 1956)

Collection of pathogenic and vaccine microorganisms of animals of Kovalenko Institute of Experimental Veterinary (in Russian)

Collection of rhizosphere microorganisms of the Institute of Biochemistry and Physiology of Plants and Microorganisms - Russian Academy of Sciences

(untitled) - Yegorenkova, I. V.; Tregubova, K. V.; Matora, L. Y.; Burygin, G. L.; Ignatov, V. V. (Curr. Microbiol., 2010)